2013
DOI: 10.1007/s10461-013-0547-4
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Role of Food Insecurity in Adherence to Care and Treatment Among Adult and Pediatric Populations Living with HIV and AIDS

Abstract: Adherence to antiretroviral therapy (ART) is critical for reducing HIV/AIDS morbidity and mortality. Food insecurity (FI) is emerging as an important barrier to adherence to care and treatment recommendations for people living with HIV (PLHIV), but this relationship has not been comprehensively examined. Therefore, we reviewed the literature to explore how FI may impact ART adherence, retention in medical care, and adherence to health care recommendations among PLHIV. We found data to support FI as a critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
179
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(210 citation statements)
references
References 105 publications
8
179
1
7
Order By: Relevance
“…It was found to be directly associated with VAS adherence and pill counts. This is in agreement with numerous studies and a meta-analysis [46][47][48] which have reported an association between food insecurity and ART adherence. Food insecurity has been found to be associated with poor antiretroviral adherence among people living with HIV (PLHIV) [49].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was found to be directly associated with VAS adherence and pill counts. This is in agreement with numerous studies and a meta-analysis [46][47][48] which have reported an association between food insecurity and ART adherence. Food insecurity has been found to be associated with poor antiretroviral adherence among people living with HIV (PLHIV) [49].…”
Section: Discussionsupporting
confidence: 93%
“…Food insecurity has been found to be associated with poor antiretroviral adherence among people living with HIV (PLHIV) [49]. Other studies have established strong relationship between food insecurity and non-adherence [48]. Using unannounced pill counts and pharmacy refill, Kalichman et al [50] and Weiser et al [49] found an association between food insecurity and non-adherence among urban poor PLHIV in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…In this section Young et al [24] review the role of food insecurity in adherence to care and treatment among adult and paediatric populations living with HIV. O' HIarlaithe et al [25] review and propose a classification of the barriers preventing women from accessing maternal and newborn child health (MNCH) and prevention of motherto-child transmission (PMTCT) services (Table 1).…”
Section: Adherence Food Security and Nutritionmentioning
confidence: 99%
“…• Food insecurity has been found to be a critical barrier to adherence to ART and care among HIV-infected adults, HIV-infected pregnant women and their HIVexposed infants, and child and adolescent PLHIV in both qualitative and quantitative studies [24] • Mechanisms to explain the linkages between food insecurity and ART non-adherence include: the exacerbation of hunger, ART side effects in the absence of adequate food and competing resource demands [24] • Interventions that address food insecurity may improve adherence to care and treatment for PLHIV [24] • Increased coverage or uptake of PMTCT services can be achieved if policy makers and programme managers understand access barriers [25] • Barriers to accessing PMTCT (Table 1) include social norms and knowledge, socioeconomic status, physiological status and psychological conditions. Economic and social factors are some of the most common demand side barriers.…”
Section: Adherence Food Security and Nutritionmentioning
confidence: 99%
“…Food insecurity, although generally thought of as an outcome of financial or resource constraints (Baer et al 2015), is also found to be affected by behavioral aspects (Timmer 2012). Previous studies have outlined the impact of proximate socioeconomic stressors such as poverty and food vulnerability on HSB (Sundari Ravindran 2014;Young et al 2014). It is, therefore, assumable that women who face hardships to secure food will face the trade-off between nutrition and medical care that will eventually lead to non-or under-utilization of maternal healthcare.…”
Section: Introductionmentioning
confidence: 99%